"Dampness" and "Dryness": What is important for children's allergies? A cross-sectional study of 7366 children in northeast Chinese homes. (July 2018) - Sun, Yuexia; Hou, Jing; Kong, Xiangrui; Zhang, Qingnan; Wang, Pan; Weschler, Louise B.; Sundell, Jan
Abstract: This study investigates associations of building dampness indicators, and perceptions of moldy odor, humidity and dryness (Dampness and Dryness, D&D) with children's asthma and allergies. Data were obtained from a cross-sectional study in Tianjin and Cangzhou, China from 2013 to 2014. Completed surveys were returned by 7366 families with children 0–8 years old. We studied D&D factors both in the current residence and the residence where the children lived immediately after birth. A total of 4.4% of the children had doctor-diagnosed asthma; 9.5% had doctor-diagnosed rhinitis; and 39.1% had doctor-diagnosed eczema. Most of the dampness indicators, perceptions of odors, and perceived dryness, were significantly associated with children's asthma and allergies. A reporting bias in parents (or guardians) who themselves had allergies was not found to be the reason for the associations between D&D and health effects. Compared with either previous or current exposure to D&D, continuous exposure to D&D was a greater risk for children's asthma and allergies. Perceived dryness was the most important studied risk factor for children's allergies in either current or previous homes. Highlights: Both perceived dampness and perceived dryness are risks for asthma and allergy. Perceived dryness is associated with the greatest risk of asthma and allergy. Prevalence is greater for entire life exposure than for one of two residences. No difference in prevalence between children of allergic or non-allergic parents. Perceived dryness appears to be a proxy for polluted indoor air.